Indigenous women’s experiences about the pregnancy-puerperal cycle - Lubiane Boer; Francisca Georgina Macedo de Sousa; Rizioléia Marina Pinheiro Pina; Margarita Poblete; Léris Salete Bonfanti Haeffner; Dirce Stein Backes (Revista Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to understand the experiences of indigenous women regarding the pregnancy-puerperal cycle. Methods: qualitative, exploratory and descriptive research, carried out between May and August 2023 with 27 pregnant women from Indigenous Villages in Mato Grosso, Brazil, through open individual interviews. The data was analyzed using Reflexive thematic analysis. Results: data analysis resulted in the following themes: Cultivation of labor and birth in its natural and sacred path; Unique practices and beliefs associated with breastfeeding; Evolved or reductive thinking? The participants suggest inviolable practices and beliefs, which must be welcomed, respected and enhanced by indigenous health teams. Final Considerations: the experiences of indigenous women regarding the pregnancy-puerperal cycle are unique and motivated by inviolable cultural and religious beliefs, which transcend scientific knowledge, certainties and the linearity of contemporary approaches, normally established as order.